2013
DOI: 10.1016/j.bbrc.2013.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A stimulates macrophage foam cell formation via lectin-like oxidized low-density lipoprotein receptor 1 upregulation

Abstract: Elevated levels of serum amyloid A (SAA) is a risk factor for cardiovascular diseases, however, the role of SAA in the pathophysiology of atherosclerosis remains unclear. Here we show that SAA induced macrophage foam cell formation. SAA-stimulated foam cell formation was mediated by c-jun N-terminal kinase (JNK) signaling. Moreover, both SAA and SAA-conjugated high density lipoprotein stimulated the expression of the important scavenger receptor lectin-like oxidized low-density lipoprotein receptor 1 (LOX1) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…As a result, SAA binding to HDL alters its protective function against the development of atherosclerosis [6, 36]. Previous studies have reported that SAA could enhance oxidized LDL-induced foam cell formation, which plays an important role in the pathogenesis of atherosclerosis [37]. Although the epigenetic regulation of this process remains unclear, Jmjd3 expression was increased in patients with familial hypercholesterolemia (FH) compared with healthy individuals [38] (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, SAA binding to HDL alters its protective function against the development of atherosclerosis [6, 36]. Previous studies have reported that SAA could enhance oxidized LDL-induced foam cell formation, which plays an important role in the pathogenesis of atherosclerosis [37]. Although the epigenetic regulation of this process remains unclear, Jmjd3 expression was increased in patients with familial hypercholesterolemia (FH) compared with healthy individuals [38] (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the effect of Jmjd3 in sterile inflammation, it is reported that Jmjd3 could mediate IL-6 gene regulation in endothelial cells following spinal cord injury [44]. Previously, it was shown that up-regulation of SAA in the blood circulation could enhance the induction of foamy macrophage formation by oxLDL and thus implicates SAA as a potential causal agent in atherogenesis [37]. In this study, we showed that attenuated macrophage foam cell formation could result from dampened proinflammatory gene induction in cells with Jmjd3 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 11 Because lymphocyte apoptosis in the spleen are markedly induced during the pathogenesis of sepsis, leading to immune paralysis in sepsis patients, we investigated whether SMFM had any effect on this process. CLP surgery caused increases in apoptosis, as detected by DNA fragmentation analysis (TUNEL assay), of splenocytes, (Fig.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Mouse bone marrow-derived macrophages were generated as described previously (11). Mouse bone marrow-derived macrophages were incubated with vehicle (0.1% DMSO in PBS) or SMFM (200 µg/ml) for 30 min.…”
Section: Cytokine Release From Bone Marrow-derived Macrophagesmentioning
confidence: 99%
“…When macrophages are exposed to SAA-containing HDL, they turn into foam cells in a dose-dependent manner69 as a consequence of increased uptake of LDL69 and increased uptake and hydrolysis of cholesteryl esters from SAA-containing HDL 70. Foam cells are cholesterol-loaded macrophages that are a principal component of plaques.…”
Section: Saa Protein Function In Hdlmentioning
confidence: 99%